2013
DOI: 10.1016/j.destud.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study on the use of digital sculpting in conceptual product design

Abstract: ElsevierAlcaide Marzal, J.; Diego-Mas, JA.; Asensio Cuesta, S.; Piqueras Fiszman, B. (2013). An exploratory study on the use of digital sculpting in conceptual product design. Design Studies. 34(2):264-284. doi:10.1016/j.destud.2012.09.001. An Exploratory Study on the Use of Digital Sculpting in Conceptual Product Design AbstractThe product design process involves intensive manipulation of graphical data, from pencil sketches to CAD files. The use of graphic software is common among professionals in this field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 44 publications
1
39
0
5
Order By: Relevance
“…Verstijnen et al (1998), Do (2005) and Babapour 2015)to develop CAD tools that better support designers' ideation processes, using the knowledge gained from studying sketching. Researchers have argued that if CAD tools are to compete with sketching, they must be intuitive, allow ambiguous representations and e ortless exploration of ideas and be able to capture sudden thoughts and ideas (Alcaide-Marzal et al, 2013;Hacker et al, 2002;Pei et al, 2009;Séquin, 2004;Verstijnen et al, 1998). However, when exploring the use of available CAD tools, many studies have found that CAD tools have limited to no use in design ideation.…”
Section: Cad Tools In Design Ideationmentioning
confidence: 99%
See 3 more Smart Citations
“…Verstijnen et al (1998), Do (2005) and Babapour 2015)to develop CAD tools that better support designers' ideation processes, using the knowledge gained from studying sketching. Researchers have argued that if CAD tools are to compete with sketching, they must be intuitive, allow ambiguous representations and e ortless exploration of ideas and be able to capture sudden thoughts and ideas (Alcaide-Marzal et al, 2013;Hacker et al, 2002;Pei et al, 2009;Séquin, 2004;Verstijnen et al, 1998). However, when exploring the use of available CAD tools, many studies have found that CAD tools have limited to no use in design ideation.…”
Section: Cad Tools In Design Ideationmentioning
confidence: 99%
“…Early studies concluded that CAD tools of the time did not live up to the requirements of design ideation and were only useful for the later stages of the design process (Stappers and Hennessey, 1999;Verstijnen et al, 1998). Later studies have found that pen-and-paper sketching is better for generating solutions (Alcaide-Marzal et al, 2013;Stones and Cassidy, 2007), reinterpretation (Alcaide-Marzal et al, 2013;Stones and Cassidy, 2010) and conceiving the problem (Bilda and Demirkan, 2003). One of the major reasons CAD tools are deemed unsuited for ideation is that they are argued to not support ambiguous representations (van Dijk, 1995;Hennessey and Stappers, 1999;Verstijnen et al, 1998) and therefore cannot enable the conversation with the material that allows the designer to see new directions for her original thought (Charlesworth, d.…”
Section: Cad Tools In Design Ideationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Séquin (2005) showed how digital media could allow designers to explore a wide range of design alternatives through computation and programming. In another study, a digital sculpting medium was found suitable for the ideation phase, due to its restricted precision, which enabled the designers to carry out activities similar to that of sketching in terms of the number of ideas and reinterpretations (Alcaide-Marzal, Diego-Más, Asensio-Cuesta et al, 2012). Digital modelling media -Computer-aided media differ in the particular approaches that they allow for working with digital models (e.g.…”
Section: Building Separate Components From Different Materials and Inmentioning
confidence: 99%